1996
DOI: 10.1037/0012-1649.32.4.717
|View full text |Cite
|
Sign up to set email alerts
|

Parenting behaviors and the occurrence and co-occurrence of adolescent depressive symptoms and conduct problems.

Abstract: This study of 388 adolescents found a significant covariation between the elevated depressive symptoms and conduct problems. Observer ratings of family interaction indicate that (a) parents of I Oth graders with and without later adjustment problems differed in their parenting behaviors when the adolescents were in 7th, 8th, and 9th grades; (b) parents of 10th graders with elevated conduct problems were more hostile than parents of I Oth graders with elevated depressive symptoms when the adolescents were in 7t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
205
3
7

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(239 citation statements)
references
References 63 publications
20
205
3
7
Order By: Relevance
“…Although parental hostility has most often been studied in the context of child externalizing problems, some researchers have proposed that repeated hostile confrontations with irritable parents represent a salient daily stressor that increases the child's psychological distress, diminishes the child's sense of self, and heightens feelings of hopelessness and worthlessness, all of which are symptoms of internalizing problems (Burge & Hammen, 1991;Downey & Coyne, 1990;Ge et al, 1996). Several empirical investigations have borne out this hypothesis.…”
Section: Individual Parenting Behaviorsmentioning
confidence: 99%
“…Although parental hostility has most often been studied in the context of child externalizing problems, some researchers have proposed that repeated hostile confrontations with irritable parents represent a salient daily stressor that increases the child's psychological distress, diminishes the child's sense of self, and heightens feelings of hopelessness and worthlessness, all of which are symptoms of internalizing problems (Burge & Hammen, 1991;Downey & Coyne, 1990;Ge et al, 1996). Several empirical investigations have borne out this hypothesis.…”
Section: Individual Parenting Behaviorsmentioning
confidence: 99%
“…The questionnaire was developed by the Iowa Youth and Families Project based on their observational measures of the same constructs (e.g. Ge et al, 1996), with high internal reliability and good correlations with observed parental warmth and hostility. In the present study, the nine-item warmth scale had internal consistency reliability of 0.91, and the 15-item hostility scale had ALPHA=0.92.…”
Section: Child Report Of Mother Warmth and Hostilitymentioning
confidence: 99%
“…First, although CD, ODD, ADHD, and depression undoubtedly have unique causal influences, there is evidence from twin studies that CD shares common genetic influences with ADHD (Coolidge, Thede, & Young, 2000;Thapar, Harrington, & McGuffin, 2001), with ODD (Coolidge et al, 2000;Eaves et al, 2000), and with depression (O'Connor, McGuire, Reiss, Hetherington, & Plomin, 1998). Second, there is evidence that CD shares common environmental risk factors with ODD and depression, such as negativity among family members and parenting that is low in warmth and monitoring (Fergusson, Lynskey, & Horwood, 1996;Frick et al, 1992;Ge, Best, Conger, & Simons, 1996;Goodman & Gotlib, 1999;Goodman et al, 1998;Pike, McGuire, Hetherington, Reiss, & Plomin, 1996). Third, there is evidence consistent with the hypothesis that childhood CD leads to family and peer rejection and academic failure, which give rise to depressive symptoms (Capaldi, 1992;Patterson & Capaldi, 1990;Patterson & Stoolmiller, 1991).…”
mentioning
confidence: 99%